2002
DOI: 10.1159/000064680
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion Abnormalities Early (12–24 h) after Coronary Stenting or Balloon Angioplasty: Implications Regarding Pathophysiology and Late Clinical Outcome

Abstract: Objective: We prospectively examined the prevalence of reversible perfusion defects on very early (12–24 h) thallium-201 single photon emission computed tomography (SPECT) scintigraphy after angiographically successful percutaneous coronary intervention (PCI) by stenting and/or stand-alone balloon angioplasty and the predictive value of these defects for late target lesion revascularization (TLR). Patients and Methods: 83 consecutive patients undergoing PCI for 88 lesions (38 balloon angioplasties, 50 stents) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
6
0
3
Order By: Relevance
“…Our findings are consistent with those of studies which found that myocardial perfusion imaging predicts late restenosis [3,8,9,23]. Moreover, our binary logistic regression analysis incorporating nine possible .016 * SDS, summed differential score; tREV, mean territorial reversibility; tSDS, territorial summed differential score; *, significant determinants of late restenosis, identified only the presence of a reversible perfusion defect on M-SPECT after stent implantation as an independent predictor (P \ 0.05).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are consistent with those of studies which found that myocardial perfusion imaging predicts late restenosis [3,8,9,23]. Moreover, our binary logistic regression analysis incorporating nine possible .016 * SDS, summed differential score; tREV, mean territorial reversibility; tSDS, territorial summed differential score; *, significant determinants of late restenosis, identified only the presence of a reversible perfusion defect on M-SPECT after stent implantation as an independent predictor (P \ 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been found by other studies. Jaffe et al [9] evaluated the incidence of reversible perfusion defects after balloon angioplasty and stenting, and found that they were very similar (32% for balloon angioplasty and 36% for stenting; p = NS). Nagaoka et al [10] also observed reversible defects in 36% of patients by M-SPECT four days after stent implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When MPI is performed very early after angioplasty or stenting (within 24 - 48 hours), it may exhibit defects in the absence of stenoses. These early defects may be due to abnormal endothelium function which is common after angioplasty and may cause transiently impaired coronary flow reserve after intervention, while the prognostic significance of these defects is uncertain [21]. Some authors found that the incidence of restenosis was 52% to 75% in patients with reversible defects on early (<2 months after PCI) imaging, compared with an incidence of 12% to 17% in those with normal perfusion and thus they stated that MPI performed early after PCI could predict future restenosis [22].…”
Section: Restenosismentioning
confidence: 99%
“…Este mesmo autor demonstrou redução da incidência, extensão e gravidade da hipoperfusão transitória pós-aterectomia com o uso do bloqueador da GPIIb/IIIa, o que sugere que a agregação plaquetária, realmente, tenha papel importante na etiologia das alterações perfusionais precoces após RP com aterectomia 9 . Em outro estudo que analisou pacientes após angioplastia ou colocação de stent, os achados perfusionais na CM, nas primeiras 24 horas do procedimento, não predizeram a necessidade de nova revascularização tardia 10 . Outro aspecto importante a ser considerado é o trauma e provável disfunção endotelial associada como causa de alterações perfusionais transitórias.…”
Section: Utilidade Da Cintilografia Miocárdica Na Avaliação De Pacienunclassified